Man with a past [large type] - Krentz, Jayne Ann (Thorndike/Chivers, 2004)
Cole Stockton had a will of steel and a raw determination to go after what he wanted - including Kelsey Murdock. He'd invaded her life, assaulting her with his sensuality, tempting her to be reckless. She sensed something dangerous about the man - in the secrets he refused to share, the past that still haunted him, the coiled tension that denied intimacy. For Cole, the past was a closed door. For Kelsey, that meant too many questions and no answers - and the best reason to walk away, before it was too late. But when a simple business trip turns into a dangerous survival game, she is plunged into a world Cole knows all too well. Now Kelsey must trust he knows it well enough to keep them both alive.